2015
DOI: 10.1111/hpb.12347
|View full text |Cite
|
Sign up to set email alerts
|

Renal function after low central venous pressure‐assisted liver resection: assessment of 2116 cases

Abstract: The majority of patients in the study cohort had low baseline eGFR. Biochemical alterations in eGFR are transient in the vast majority of patients after LCVP-assisted hepatectomy and their clinical impact is limited. The present data suggest that clinically relevant renal dysfunction is a very uncommon event in patients undergoing LCVP-assisted liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 33 publications
3
30
0
1
Order By: Relevance
“…Our findings are congruent with those reported by Correa-Gallego 17) . They reported that low central venous pressure-assisted hepatectomy was associated with AKI (17%).…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are congruent with those reported by Correa-Gallego 17) . They reported that low central venous pressure-assisted hepatectomy was associated with AKI (17%).…”
Section: Discussionsupporting
confidence: 94%
“…Twenty years ago, our group developed and reported a simple, effective and reproducible technique for decreasing the intraoperative blood loss in patients undergoing liver resection. [19] LCVP-assisted liver resection resulted in improved outcomes and has become the standard approach at our institution [20, 21] and others. [25-28] The success of this approach hinges on effective communication between the anesthesia and surgical teams during the operative and perioperative periods.…”
Section: Discussionmentioning
confidence: 99%
“…Once hemostasis has been achieved, infusion of an assumed volume of required resuscitation restores euvolemia. This approach while proven safe,[21] may under or overestimate the fluid needs of these patients and may not provide the optimal amount of resuscitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the long surgery duration of ~380 min during the first stage of ALPPS, along with the adverse effects of anesthesia and surgical stress on renal function possibly increased the risk and contributed to the development of acute kidney injury. Of patients undergoing the ALPPS procedure, 70% of cases presented liver metastasis from colorectal cancer, ~17% of patients presented primary liver cancer (2,10,11), and a small number of patients had liver cancer secondary to hepatitis-induced cirrhosis. The latter group of patients are more likely to suffer with viral nephropathy and are at a high risk of postoperative acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%